Between the heart and the mind – psychological aspects of cardiologic diseases - Janowska, Małgorzata; Czernikiewicz, Andrzej; Janowski, Marcin (Current Problems of Psychiatry, 2015)
The first attempts to understand the relationship between the body and the mind date back to the beginning of the 20th century. However, psychological factors affecting medical conditions have not been identified so far. It is believed that psychosomatic disorders result from ‘conversion’ of unexpressed emotions into physical symptoms. Unexpressed emotions are associated with a number of changes in the activity of systems that maintain homeostasis of the body. The result is a constant activation of the hypothalamic-pituitary-adrenal axis, increased activity of sympathetic system and impaired activity of parasympathetic system. Among many psychosomatic disorders, cardiovascular diseases, including coronary heart disease (CHD), deserve particular attention. Risk factors include not only commonly known hypertension, obesity, hyperlipidaemia and smoking but also psychological factors, such as personality type, alexithymia ( inability to identify and verbally describe emotions) and comorbid psychiatric disorders. It is believed that type D personality (main traits include social inhibition, negative affectivity), high level of alexithymia and comorbid depressive disorder may lead to the development of coronary heart disease. An investigation of the relationship between the mind and the body is an interdisciplinary challenge for modern medicine. Increasing the role of socio-emotional factors in the pathogenesis of somatic diseases, including coronary heart disease, paves the way to the discovery of psychological factors in the development of somatic diseases and to the change of behaviour, which improves prognosis and the quality of life.